Implementation of an Object-Oriented Goods Inventory Application at PT XYZ - Setiawan, Restu Aji; Anita Dewi, Supriyati; Akhmad, Fathir; Faisal Yahya, Muthasina; Muhammad, Darwis (INTI International University, 2023)
Effective and efficient inventory system management is very important in a company. PT XYZ is still doing manual recording in the process of managing its goods. The purpose of this research is to develop an inventory application to facilitate the management of goods and the preparation of reports. The method used in application development is Object-Oriented Programming (OOP) which can be done modularly and is easier to maintain. The data collection method is carried out by direct observation and study of relevant research literature. The application testing uses the Black Box method which has met expectations, menu features and objects run according to design. This research produces an inventory application that can make the inventory process at PT XYZ more effective based on test results which show that all application functions are running well